Alterations of Phagocytic Activity and Capacity in Granulocytes and Monocytes Depend on the Pathogen Strain in Porcine Polytrauma - Jan Tilmann Vollrath; Felix Klingebiel; Felix Klingebiel; Felix Klingebiel; Felix Marius Bläsius; Johannes Greven; Eftychios Bolierakis; Andrea Janicova; Ildiko Rita Dunay; Frank Hildebrand; Ingo Marzi; Borna Relja (Frontiers in Medicine, 2021)
Background: Polytraumatized patients undergo a strong immunological stress upon insult. Phagocytes (granulocytes and monocytes) play a substantial role in immunological defense against bacteria, fungi and yeast, and in the clearance of cellular debris after tissue injury. We have reported a reduced monocytes phagocytic activity early after porcine polytrauma before. However, it is unknown if both phagocyte types undergo those functional alterations, and if there is a pathogen-specific phagocytic behavior. We characterized the phagocytic activity and capacity of granulocytes and monocytes after polytrauma.Methods: Eight pigs (Sus scrofa) underwent polytrauma consisting of lung contusion, liver laceration, tibial fracture and hemorrhagic shock with fluid resuscitation and fracture fixation with external fixator. Intensive care treatment including mechanical ventilation for 72 h followed. Phagocytic activity and capacity were investigated using an in vitro ex vivo whole blood stimulation phagocytosis assays before trauma, after surgery, 24, 48, and 72 h after trauma. Blood samples were stimulated with Phorbol-12-myristate-13-acetate and incubated with FITC-labeled E. coli, S. aureus or S. cerevisiae for phagocytosis assessment by flow cytometry.Results: Early polytrauma-induced significant increase of granulocytes and monocytes declined to baseline values within 24 h. Percentage of E. coli-phagocytizing granulocytes significantly decreased after polytrauma and during further intensive care treatment, while their capacity significantly increased. Interestingly, both granulocytic phagocytic activity and capacity of S. aureus significantly decreased after trauma, although a recovery was observed after 24 h and yet was followed by another decrease. The percentage of S. cerevisiae-phagocytizing granulocytes significantly increased after 24 h, while their impaired capacity after surgery and 72 h later was detected. Monocytic E. coli-phagocytizing percentage did not change, while their capacity increased after 24–72 h. After a significant decrease in S. aureus-phagocytizing monocytes after surgery, a significant increase after 24 and 48 h was observed without capacity alterations. No significant changes in S. cerevisiae-phagocytizing monocytes occurred, but their capacity dropped 48 and 72 h.Conclusion: Phagocytic activity and capacity of granulocytes and monocytes follow a different pattern and significantly change within 72 h after polytrauma. Both phagocytic activity and capacity show significantly different alterations depending on the pathogen strain, thus potentially indicating at certain and possibly more relevant infection causes after polytrauma.